The Application of HACCP (Hazard Analysis Critical Control Point) in Croissant Production Process in CV. P-RS – Bali - Singapurwa, Ni Made Ayu Suardani; Semariyani, A.A. Made; Candra, I Putu; Rudianta, I Nyoman; Arandini, Putu Chiana Adi (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2022)
CV. P-RS is a company engaged in the production of pastry, bakery, and also pastry & bakery one of Croissant, ingredients provider. Croissant is a type of pastry (laminated roll-in fat), more precisely folded pastry covered with fat (korsvet) or butter with the addition of yeast in the dough. Most of its products are distributed to hotels, restaurants, cafes, catering and retail throughout the island of Bali. Therefore, the quality of all their products is guaranteed. The implementation of an Integrated Quality Management program based on the concept of HACCP (Hazard Analysis Critical Control Point) must be applied in the entire series of handling and processing processes. The implementation of the HACCP food safety management system in CV. P-RS has been running in accordance with SNI 01-4852-1998 regarding the hazard analysis system and critical point control (HACCP) as well as guidelines for its application. The things that underlie the need for the implementation of a food safety management system in CV. P-RS is a trend in consuming safe products accompanied by meeting the needs of consumers who want safe products. Critical Control Point (CCP) of the croissant production process includes weighing of raw materials and supporting materials, metal detecting, and oven.